Assessing how biofilms modulate stream periphyton metacommunity assemblage: A translocation experiment - Daniel Zamorano; Travis Ingram; Fabio A. Labra; Christoph D. Matthaei (Ecology, 2025)
The role of three‐dimensional structural complexity in shaping communities has been increasingly studied, and evidence indicates that vertical stratification favors coexistence through niche partitioning. Despite the clear relationship between three‐dimensional structure and community assemblages, its role in shaping metacommunity processes is still unclear. To address this knowledge gap, we carried out a translocation experiment using stream periphyton (benthic microalgae) as a model community. Structural complexity in stream periphyton is observed when thicker biofilms develop, reducing hydraulic stress and improving nutrient uptake, particularly for understory taxa. In this experiment, we exposed ceramic tiles in a source river for 4, 11, or 21 days, creating a biofilm biomass and successional gradient. We then translocated these tiles to 10 receiving rivers in two phosphorus enrichment categories (low, high). After 25 days, we collected all tiles and evaluated biofilm biomass and the periphyton community. We determined community similarity post‐translocation using the Bray–Curtis distance, comparing translocated tiles to pre‐translocation communities and to control tiles from the receiving rivers. Translocated tiles remained more similar to their pre‐translocation community when the source and receiving rivers were more similar to each other and when pre‐colonization time was longer (11 or 21 days), whereas biofilm biomass was not a key predictor. Further, translocated tiles became more similar to their receiving river communities when pre‐colonization time was shorter (4 days) and when receiving river biofilm biomass was higher, suggesting that neighborhood biofilm biomass could indicate local propagule pressure. Low‐phosphorus sites exhibited lower biofilm biomass and high proportions of taxa from both receiving rivers and the source river on translocated tiles, which indicated a more important role of species sorting. By contrast, high‐phosphorus sites displayed greater neighborhood biomass and translocated tiles less similar to receiving rivers or the source river due to a higher proportion of rare taxa, which suggested mass effects. This experiment expands our knowledge of the role of three‐dimensional community structure in driving metacommunity processes by considering environmental contexts, biomass as a proxy of structural complexity, and successional time.

Ecological role of marine mammals in the Magellan Strait: Insights from trophic modeling - Daniela Haro; Fabio A. Labra; Sergio Neira; Juan Carlos Hernández-Padilla; Francisco Arreguín-Sánchez (Ecological Modelling, 2025)

Landscape fragmentation constrains bumblebee nutritional ecology and foraging dynamics - E. Pioltelli; L. Guzzetti; M. Ouled Larbi; M. Labra; A. Galimberti; P. Biella (Landscape and Urban Planning, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Robust automatic net damage detection and tracking on real aquaculture environment using computer vision - Julio Labra; Marcos D. Zuniga; Javier Rebolledo; Mohamed A. Ahmed; Rodrigo Carvajal; Nicolás Jara; Gonzalo Carvajal (Aquacultural Engineering, 2023)

Acidification and high-temperature impacts on energetics and shell production of the edible clam Ameghinomya antiqua - Sebastián I. Martel; Carolina Fernández; Nelson A. Lagos; Fabio A. Labra; Cristián Duarte; Juan F. Vivanco; Claudio García-Herrera; Marco A. Lardies (Frontiers in Marine Science, 2022)
Warming and ocean acidification are currently critical global change drivers for marine ecosystems due to their complex and irreversible effects on the ecology and evolution of marine communities. Changes in the chemistry and the temperature of the ocean impact the biological performance of marine resources by affecting their energy budget and thus imposing energetic restrictions and trade-offs on their survival, growth, and reproduction. In this study, we evaluated the interplaying effects of increased p CO 2 levels and temperature on the economically relevant clam Ameghinomya antiqua , an infaunal bivalve inhabiting a wide distributional range along the coast of Chile. Juvenile clams collected from southern Chile were exposed to a 90-day experimental set-up emulating the current and a future scenario projeced to the end of the current century for both high p CO 2 /low-pH and temperature (10 and 15°C) projected for the Chilean coast. Clams showed physiological plasticity to different projected environmental scenarios without mortality. In addition, our results showed that the specimens under low-pH conditions were not able to meet the energetic requirements when increased temperature imposed high maintenance costs, consequently showing metabolic depression. Indeed, although the calcification rate was negative in the high- p CO 2 scenario, it was the temperature that determined the amount of shell loss. These results indicate that the studied clam can face environmental changes for short-term periods modifying energetic allocation on maintenance and growth processes, but with possible long-term population costs, endangering the sustainability of an important benthic artisanal fisheries resource.

Agrobacterium rhizogenes-mediated transformation of grain (Amaranthus hypochondriacus) and leafy (A. hybridus) amaranths - Andrea P. Castellanos-Arévalo; Andrés A. Estrada-Luna; José L. Cabrera-Ponce; Eliana Valencia-Lozano; Humberto Herrera-Ubaldo; Stefan de Folter; Alejandro Blanco-Labra; John P. Délano-Frier (Plant Cell Reports, 2020)

The Importance of Intraspecific Variation for Niche Differentiation and Species Distribution Models: The Ecologically Diverse Frog Pleurodema thaul as Study Case - Aura M. Barria; Daniel Zamorano; Andrés Parada; Fabio A. Labra; Sergio A. Estay; Leonardo D. Bacigalupe (Evolutionary Biology, 2020)

Assessing how body size affects the species-time relationship in a shallow marine benthic megafauna community exposed to a strong hypoxia disturbance - Fabio A. Labra; Eduardo Hernández-Miranda; Renato A. Quiñones (Marine Biology, 2020)

Learning-by-consequence foraging model of the Northern Mealy Amazon in a modified landscape of tropical moist forest - Miguel A. De Labra-Hernández; Katherine Renton (Journal of Ornithology, 2019)

Resilience of an aquatic macrophyte to an anthropogenically induced environmental stressor in a Ramsar wetland of southern Chile - Eduardo Jaramillo; Cristian Duarte; Fabio A. Labra; Nelson A. Lagos; Bruno Peruzzo; Ricardo Silva; Carlos Velasquez; Mario Manzano; Daniel Melnick (Ambio, 2019)

The relative role of ecological interactions and environmental variables on the population dynamics of marine benthic polychaetes - Fabio A. Labra; Rodrigo A. Moreno; Sergio A. Alvarado; Franklin D. Carrasco; Sergio A. Estay; Marcelo M. Rivadeneira (Marine Biodiversity, 2018)

Trend and recovery of the total ozone column in South America and Antarctica - Richard Toro A.; Consuelo Araya; Felipe Labra O.; Luis Morales; Raúl G. E. Morales; Manuel A. Leiva G. (Climate Dynamics, 2017)

Life With or Without Names - M. Casiraghi; A. Galimberti; A. Sandionigi; A. Bruno; M. Labra (Evolutionary Biology, 2016)

Evaluating the efficacy of restoration plantings through DNA barcoding of frugivorous bird diets - A. Galimberti; S. Spinelli; A. Bruno; V. Mezzasalma; F. De Mattia; P. Cortis; M. Labra (Conservation Biology, 2016)
Frugivores are critical components of restoration programs because they are seed dispersers. Thus, knowledge about bird–plant trophic relationships is essential in the evaluation of the efficacy of restoration processes. Traditionally, the diet of frugivores is characterized by microscopically identifying plant residues in droppings, which is time‐consuming, requires botanical knowledge, and cannot be used for fragments lacking detectable morphological characteristics (e.g., fragmented seeds and skins). We examined whether DNA barcoding can be used as a universal tool to rapidly characterize the diet of a frugivorous bird, Eurasian blackcap ( Sylvia atricapilla ). We used the DNA barcoding results to assess restoration efforts and monitor the diversity of potentially dispersed plants in a protected area in northern Italy. We collected 642 Eurasian Blackcap droppings at the restored site during the autumn migration over 3 years. Intact seeds and fragmented plant material were analyzed at 2 plastidial barcode loci ( rbcL and trnH‐psbA ), and the resulting plant identifications were validated by comparison with a reference molecular data set of local flora. At least 17 plant species, including 7 of the 11 newly transplanted taxa, were found. Our results demonstrate the potential for DNA barcoding to be used to monitor the effectiveness of restoration plantings and to obtain information about fruit consumption and dispersal of invasive or unexpected plant species. Such an approach provides valuable information that could be used to study local plant biodiversity and to survey its evolution over time.

A rapid diagnostic approach to identify poisonous plants using DNA barcoding data - S. Federici; D. Fontana; A. Galimberti; I. Bruni; F. De Mattia; P. Cortis; G. Galasso; M. Labra (Plant Biosystems, 2015)

Analytical approaches for DNA barcoding data – how to find a way for plants? - A. Sandionigi; A. Galimberti; M. Labra; E. Ferri; E. Panunzi; F. De Mattia; M. Casiraghi (Plant Biosystems, 2012)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Phylogeographical structure and conservation genetics of wild grapevine - F. Grassi; M. Labra; S. Imazio; R. Ocete Rubio; O. Failla; A. Scienza; F. Sala (Conservation Genetics, 2006)

Chloroplast Microsatellites to Investigate the Origin of Grapevine - S. Imazio; M. Labra; F. Grassi; A. Scienza; O. Failla (Genetic Resources and Crop Evolution, 2006)

Evidence of a secondary grapevine domestication centre detected by SSR analysis - F. Grassi; M. Labra; S. Imazio; A. Spada; S. Sgorbati; A. Scienza; F. Sala (Theoretical and Applied Genetics, 2003)

Chemical Composition of Precloacal Secretions of Two Liolaemus fabiani Populations: Are They Different? - Claudio M. Escobar; Carlos A. Escobar; Antonieta Labra; Hermann M. Niemeyer (Journal of Chemical Ecology, 2003)

Dispersal and transient dynamics in metapopulations - Fabio A. Labra; Nelson A. Lagos; Pablo A. Marquet (Ecology Letters, 2003)
Recent studies of spatially explicit metapopulation models have shown the existence of complex transient behaviour (supertransients and mesotransients) characterized by spontaneous changes in the system's dynamics after thousands or hundreds of generations, respectively. Their detection in simple ecological models has been taken as evidence that transient dynamics may be common in nature. In this study, we explore the generality of these phenomena in a simple one‐dimensional spatially explicit metapopulation model. We investigate how frequently supertransient behaviour emerges in relation to the shape and type of the dispersal kernel used (normal and Laplace), system size, boundary conditions and how sensitive they are to initial conditions. Our results show that supertransients are rare, are heavily affected by initial conditions and occur for a small set of dispersal parameter values, which vary according to kernel type, system size, and boundary conditions. Similarly, mesotransients emerge over a very narrow range of dispersal parameter values and are rare under all circumstances. Thus, transient dynamics are not likely to be either common or widespread in simple models of ecological systems.

Chemical Composition of Precloacal Secretions of Liolaemus Lizards - Carlos A. Escobar; Antonieta Labra; Hermann M. Niemeyer (Journal of Chemical Ecology, 2001)

The use of AFLP and SSR molecular markers to decipher homonyms and synonyms in grapevine cultivars: the case of the varietal group known as ’’Schiave’’ - T. Fossati; M. Labra; S. Castiglione; O. Failla; A. Scienza; F. Sala (Theoretical and Applied Genetics, 2001)